2008
DOI: 10.1016/j.neuropharm.2008.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol inhibition of kainate receptor-mediated excitatory neurotransmission in the rat basolateral nucleus of the amygdala

Abstract: The neurobiological mechanisms governing alcohol-induced alterations in anxiety-like behaviors are not fully understood. Given that the amygdala is a major emotional center in the brain and regulates the expression of both learned-fear and anxiety, neurotransmitter systems within the basolateral amygdala represent likely mechanisms governing the anxiety-related effects of acute ethanol exposure. It is well established that, within the glutamatergic system, N-methyl-D-aspartate (NMDA)-type receptors, are partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 38 publications
3
60
1
1
Order By: Relevance
“…Previous studies have shown that acute injection of CRF into the NAC (Holahan et al 1997) or into the ventricles (Koob and Bloom 1985;Lowry et al 2009) increases locomotor activity. Likewise, local injection of CRF into the Amyg, DRN, or VTA can also have an acute activating action (Hiroi and Neumaier 2009;Kalivas et al 1987;Lack et al 2008;Lee and Tsai 1989;Meloni et al 2008;Wand 2005). However, since none of the brain regions previously associated with acute CRF-increased locomotion demonstrated an association with elevated locomotion during withdrawal after the ADE (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that acute injection of CRF into the NAC (Holahan et al 1997) or into the ventricles (Koob and Bloom 1985;Lowry et al 2009) increases locomotor activity. Likewise, local injection of CRF into the Amyg, DRN, or VTA can also have an acute activating action (Hiroi and Neumaier 2009;Kalivas et al 1987;Lack et al 2008;Lee and Tsai 1989;Meloni et al 2008;Wand 2005). However, since none of the brain regions previously associated with acute CRF-increased locomotion demonstrated an association with elevated locomotion during withdrawal after the ADE (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Brain regions implicated in CRF-induced and ethanol withdrawal-induced anxiety-like behavior are the amygdala (Amyg) (Huang et al 2010;Knapp et al 2007;Koob 2003Koob , 2008Lack et al 2008;Overstreet et al 2006;Rassnick et al 1993;Wand 2005;Silberman et al 2009) and the dorsal raphe nucleus (DRN) (Huang et al 2010;Overstreet et al 2006). The basolateral amygdala and dorsal bed nucleus of the stria terminalis were also implicated in withdrawalinduced anxiety-like behavior following repeated CRF and stressor presentations prior to exposure to chronic ethanolcontaining diets (Huang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, intoxicated animals express decreased, not increased, anxiety-like behavior immediately after a chronic exposure despite exposure-induced increases in glutamatergic synaptic function. Because BLA glutamatergic synaptic responses are relatively insensitive to acute ethanol (Lä ck et al, 2008), the maintenance of an anxiolytic phenotype suggests contributions by neurotrans-mitter systems other than glutamate. In this regard, the expression of anxiety-like behavior (Sanders and Shekhar, 1995) and the activity of BLA principal neurons (Woodruff et al, 2006) are tightly regulated by GABAergic neurotransmission.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of KAR-mediated responses has been observed at quite low EtOH concentrations (Costa et al 2000;Lack et al 2008;Valenzuela et al 1998a;Weiner et al 1999). However, direct examination of KAR-mediated ion current has yielded mixed results, at least for the receptor constructs examined to date (Dildy-Mayfield and Harris 1992;Valenzuela et al 1998a).…”
Section: Ligand-gated Ion Channels and Postsynaptic Ethanol Effectsmentioning
confidence: 99%
“…EtOH also inhibits LTP induced by kainate receptor activation in the basolateral amygdala (Lack et al 2008). …”
Section: Ethanol and Synaptic Plasticitymentioning
confidence: 99%